Phase 1/2 study of intratumoral G100 (TLR4 agonist) with or without pembrolizumab in follicular lymphoma. Issue 4 (21st March 2022) - Halwani, Ahmad S.; Panizo, Carlos; Isufi, Iris; Herrera, Alex F.; Okada, Craig Y.; Cull, Elizabeth H.; Kis, Bela; Chaves, Jorge M.; Bartlett, Nancy L.; Ai, Weiyun; de la Cruz-Merino, Luis; Bryan, Locke J.; et al.
Abstract: Intratumoral injection of G100, a toll-like receptor 4 (TLR4) agonist, was shown pre-clinically to stimulate anti-tumor immune responses and tumor regression. This open-label, multicenter, phase 1/2 trial evaluated the safety, tolerability, and preliminary efficacy of intratumoral G100 injections following localized low-dose radiation in patients with follicular lymphoma (ClinicalTrials.gov #NCT02501473). The study was comprised of a G100 dose escalation (5 or 10 µg/dose, or 20 µg/dose for large tumors); a randomized component comparing G100 to G100 plus pembrolizumab; and G100 20 µg/dose expansion. Adverse events grade ≥3 were uncommon in patients treated with G100, and no unexpected toxicities were observed when combined with pembrolizumab. G100 20 µg ( n  = 18) resulted in an overall response rate of 33.3% and abscopal tumor regression in 72.2% of patients. This early-phase study provides a foundation for combining an intratumoral TLR4 agonist with agents to produce immune-mediated responses in follicular lymphoma with limited added toxicity.